FEEDING BEHAVIOUR OF SWORDFISH (XIPHOPHORUS HELLERII) AND PLATY FISH (XIPHOPHORUS MACULATUS) AS PREDATORS OF MOSQUITO LARVAE (AEDES SP.) BASED ON SCIENCE AND ISLAMIC PERSPECTIVES - Amrullah, Syarif Hidayat; Fikri, Muh; Dirhamzah, Dirhamzah (Kopertais Wilayah X Jawa Tengah, 2025)
Islam teaches the importance of maintaining the balance of nature and justice in the use of resources. Currently, one of the problems caused by human negligence due to a lack of awareness in protecting the environment is health problems. Therefore, an infectious disease that has become endemic in Indonesia is Dengue Hemorrhagic Fever (DHF). Dengue fever is caused by the dengue virus, which is transmitted through the insect vector Aedes sp. One of the controls carried out to control mosquitoes as a vector of dengue disease is to use natural predators with fish as mosquito larvae eaters. The purpose of this study is to observe the feeding behaviour and predation rate of Swordfish (Xiphophorus hellerii), and Platyfish (Xiphophorus maculatus) against mosquito larvae (Aedes sp.) and the study is based on an Islamic perspective. The observation results obtained from the feeding behaviour of X. hellerii and X. maculatus fish are that they are predators that chase, catch, and directly prey on their prey. X. hellerii fish has a higher level of feeding behaviour compared to X. maculatus fish in preying on mosquito larvae (Aedes sp.). The average predation ability of X. hellerii fish against Aedes sp. instar III larvae was 24.8 fish, while X. maculatus fish was 18.4 larvae. So that the fish X. hellerii is said to have better potential as a biocontrol to control the mosquito population, which is a vector of dengue disease, in accordance with the recommendation to maintain the balance of nature in Islamic teachings.